Еxternal forms of recombinant interferon alfa-2b - ointment and gel in the treatment of acute respiratory viral infections and influenza in children - O. V. Shamsheva; E. V. Novosad; I. V. Polesko; V. F. Uchaykin; V. V. Malinovskaya; T. A. Semenenko (Детские инфекции (Москва))
The review article presents the results of numerous studies on the effectiveness and safety of the newly developed forms of the human recombinant interferon alpha- 2b drug, ointment and gel, intended for the treatment and prevention of acute respiratory viral infections and influenza in children. Еxternal forms of the drug retain immunomodulatory, antiviral and antiproliferative effects. The dosage form of the preparation of interferon alpha-2b VIFERON® in the form of a gel or ointment allows to achieve a prolonged action due to good absorption, especially the gel, which increases its effectiveness, and also has a moisturizing effect and rarely causes allergies. All of the above properties justify the inclusion of the drug interferon alpha-2b VIFERON® in the form of a gel or ointment in the complex treatment of influenza and acute respiratory viral infections in children.